2016
DOI: 10.1542/peds.2015-4477
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poor School Readiness in Children Without Developmental Delay at Age 2

Abstract: BACKGROUND AND OBJECTIVES: Current recommendations emphasize developmental screening and surveillance to identify developmental delays (DDs) for referral to early intervention (EI) services. Many young children without DDs, however, are at high risk for poor developmental and behavioral outcomes by school entry but are ineligible for EI. We developed models for 2-year-olds without DD that predict, at kindergarten entry, poor academic performance and high problem behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 83 publications
0
42
0
1
Order By: Relevance
“…Despite the high prevalence of overweight/obesity, it is to have been expected that predictive power for this outcome would be lower without age 3 years measurement, due to biological influences. 25 Recent findings from predictive modelling studies in high-income countries, in the UK and Australia 37 and in the USA 38 corroborate the importance of social factors for later child health and development outcomes, even in high-income countries. Another study from Brazil (a middle-income country), using the 2004 Pelotas Birth Cohort, assessed a predictive model of early life factors for a cognitive outcome (low IQ) at age 6 years.…”
Section: Discussionmentioning
confidence: 86%
“…Despite the high prevalence of overweight/obesity, it is to have been expected that predictive power for this outcome would be lower without age 3 years measurement, due to biological influences. 25 Recent findings from predictive modelling studies in high-income countries, in the UK and Australia 37 and in the USA 38 corroborate the importance of social factors for later child health and development outcomes, even in high-income countries. Another study from Brazil (a middle-income country), using the 2004 Pelotas Birth Cohort, assessed a predictive model of early life factors for a cognitive outcome (low IQ) at age 6 years.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, when analysing the development of delays over time, they found that they worsened with age, especially in the two most affected domains (cognition and language). Nelson et al (2016) defined, on a nationwide scale, the large population of young children who were probably not eligible for an educational intervention but were nevertheless at high risk of having poor cognitive and behavioural out-comes upon entering nursery school. The aim was to validate two models: one of academic risk and the other of behavioural risk.…”
Section: Environmental Risk: Contextual Characteristicsmentioning
confidence: 99%
“…The role of parents' socioeconomic level can include the psychological well-being of parents (Hurr, Buetnerr, & Jeon, 2015), location of parent and child residence (Gan, Meng, & Xie, 2016), as well as parental background (Son and Peterson, 2017) which then determines the choice of the condition of the environment in which he lives. The level of education of parents who are lower than the S1 level turns out to contribute to children who do not have special needs but show problems at the beginning of school-related problems related to readiness to attend school (Nelson, et al, 2016). The level of education is also associated with the ability to obtain greater income to meet physical needs and facilitate stimulation of child development (Johnson, Martin, and Gunn, 2013).…”
Section: Parent's Adjustment In Promoting School Readiness Onmentioning
confidence: 99%